NSL Lenguaje de Simulación de Redes Neuronales Un Sistema para el modelado biológico y artificial* - Weitzenfeld, Alfredo (Revista Mexicana de Ingenieria Biomedica, 2001)
NSL (Neural Simulation Language) is a simulation system for the development of biological and artificial neural networks. NSL enables the simulation of models consisting of different levels of neural detail, from the simpler ones having only a few neurons to the more complex ones made of millions of neurons. NSL incorporates a rich environment for modeling and simulation integrating a compiled and interpreted language for efficiency and interactivity reasons, in addition to numerical libraries, graphic interfaces and visualization tools. The system is object-oriented, offering a simulation environment for inexperienced users as well as those with more programming experience. NSL has originally developed 10 years ago, having been used during this last decade for research and teaching purposes, giving rise to a number of neural models in different laboratories throughout the world. The current version, NSL 3.0, is the third generation of the system ported to different environments while based on C++ and Java programming.